Dispositional Optimism, Anxiety, Depression and Stress in a Sample of Ecuador. Inter-gender and Prediction Analysis - Gaibor-González, Ismael (2020)
Objective. To determine the inter-gender differences in dispositional optimism, depression, anxiety,and stress; as well as the predictive role of optimism on pathological features in a sample of Ecuadorian university students. Method. This is a descriptive, comparative, predictive and cross-sectional study using the Life Orientation (LOT-R) and Depression, Anxiety and Stress Scale (DASS-21) tests with 288 university students belonging to one university of Ambato; 63.9% women, 31% men aged between 17 to 39 (M = 21.6 years, SD = 2.5). Results. Gender differences were found at the Anxiety and Stress level, with greater presence in women than in men. As regards dispositional optimism and depression, gender is invariant. There were both slight and significant correlations between dispositional optimism and the dimensions evaluated by the DASS 21 test. Dispositional optimism also explains changes in variance in depression (15.2%), anxiety (9.7%) and stress (5.5%). As a conclusion, dispositional optimism is a relevant predictor of depression, as well as anxiety and stress in university students.